THE EFFECT OF LEVERAGE AND LIQUIDITY ON STOCK RETURNS WITH COMPANY SIZE AS A MODERATION IN FINANCIAL SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN THE 2020-2023 PERIOD - Fitri Rahmiyatun; Shalshabila Shafa; Sugiarti (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
The financial industry in Indonesia continues to grow through the provision of increasingly competitive investment services, opening up opportunities for companies to attract investors. This study aims to analyze the effect of leverage and liquidity on stock returns, as well as to assess whether company size strengthens this relationship. The research was conducted on non- bank financial sector companies listed on the Indonesia Stock Exchange during the period 2020–2023. A quantitative approach was used with secondary data taken from annual financial reports. The sample was determined purposively according to specific criteria, resulting in 40 observations. Data processing was performed using Eviews-13 software. Data analysis included descriptive tests, panel data regression, and moderation interaction tests (MRA). Independent variables included leverage (Debt to Equity Ratio) and liquidity (Current Ratio), with stock returns (price return) as the dependent variable, and company size (ln total assets) as the moderating variable. The results show that, both before and after MRA, leverage does not have a significant effect on stock returns (probability 0.86 & 0.56 > 0.05), and liquidity does not have a significant effect on stock returns (probability 0.12 & 0.90 > 0.05). Simultaneously, both before and after the MRA, leverage and liquidity do not have a significant effect on stock returns (probability 0.26 & 0.44 > 0.05). Furthermore, firm size does not function as a moderator in this research model, in the interaction between leverage and stock returns (probability 0.82 > 0.05), and in the interaction between liquidity and stock returns (probability 0.60 > 0.05). The coefficient of determination before MRA was 1.8% with an epsilon of 98.2%, and the coefficient of determination after MRA was 0%, indicating that the addition of moderation worsened the previous model.